Images of Undergraduate Mathematics Curriculum: A Critical Self-Reflection - Luitel, Laxman; Pant, Binod Prasad (Mathematics Education Forum Chitwan, 2021)
Higher education practices in Nepal have been playing an important role to train and develop pre-service school teachers. This paper critically reflects on the curricular and pedagogical practices of mathematics education based on the first author's experiences of learning at the undergraduate level from the perspective of mathematics curriculum images and pedagogical implications. Subscribing to autoethnography as a research methodology, we analysed the first author's experiences as an undergraduate student in one of the public campuses in Nepal which point to two major images of mathematics curriculum: curriculum as a prescription and curriculum as a cultural reproduction. Considering Habermasian Knowledge Constitutive Interest as a theoretical referent, the paper concludes that the transformation of curricular and pedagogical practices in teacher education is essential. The transformative practice in teacher education is insightful to improve pre-service and in-service school teachers' pedagogical and content knowledge in Nepal.